Islamic Education in Forming and Developing Muslim Personalities (Study of the Qur'an and Hadith) - Mukhlas (Journal of Educational Analytics, 2023)
Education aims to develop the potential of students to become human beings who believe in and fear God Almighty, have a noble character, are healthy, knowledgeable, capable, creative, independent, and democratic citizens. This study aims to explore the objectives of Islamic education in the Qur'an and Hadith in forming and developing Muslim personalities. In this study, using the type of literature review research, data sources come from two sources: primary data sources from the verses of the Qur'an and Hadith, as well as primary data sources from books and journals. data analysis using content analysis. The results of the study found that Muslim personalities formed through Islamic education contained in the Qur'an and Hadith consist of several types, namely; obedient, honest, patient, generous, and disciplined.